Aspectos morfológicos e germinativos de Eugenia velutifolia Mazine & Sobral (Myrtaceae), uma espécie endêmica do Cerrado de São Paulo. - Martins, Isabela Prestes (Universidade Federal de São Carlos, 2026)
The Myrtaceae family stands out for its high diversity and ecological importance in the Cerrado, especially the genus Eugenia, which comprises numerous species with ecological significance and economic potential. Eugenia velutifolia Mazine & Sobral is a recently described species (2019), endemic to the São Paulo Cerrado and critically endangered, lacking information regarding its reproductive biology. This study aimed to expand morphological and taxonomic data, re-evaluate its conservation status, and evaluate the species' germination capacity. Fruits were collected in a Cerrado area located in the municipality of Salto de Pirapora (SP), and the collected material (voucher) was deposited in the SORO herbarium at the Federal University of São Carlos (UFSCar), Sorocaba campus. Morphological analyses were based on fieldcollected material and herbarium specimens. The germination test was conducted at the Seedling and Seed Laboratory (LaSem) at UFSCar. The morphological description of E. velutifolia was expanded to include data regarding the bracts, bracteoles, underground system and, primarily, the fruits and seeds, which had been unknown since its original description. The fruits are predominantly rounded, measuring 3.9–13.2 × 4.05–11.7 mm, monospermic, with coloration ranging from yellow to dark purple. The seeds measure 2.95–10.7 × 2,.5–10.5 mm, are light brown, and possess an eugenioid embryo. Germination in E. velutifolia is hypogeal, starting approximately 30 days after sowing. The average germination time is 37 days, the germination success rate was 50.42%, and the germination speed index was 1.97, with variation among parent trees. Seedlings develop over a period of 75 days, which is unusual compared to other species of the genus that exhibit faster development. The endemism and anthropogenic pressure highlight the need for proper management, including propagations protocols, as well as the development of future actions for ex situ conservation to ensure the species' survival.
Morphological and germination aspects of Eugenia velutifolia Mazine & Sobral (Myrtaceae), an endemic species of the Cerrado of São Paulo.
Keywords: Conservação; Espécie ameaçada; Eugeniinae; Germinação; Propagação; Semente; Taxonomia; Conservation; Endangered species; Eugeniinae; Germination; Propagation; Seed; Taxonomy; CIENCIAS BIOLOGICAS::BOTANICA::TAXONOMIA VEGETAL; CIENCIAS BIOLOGICAS::BOTANICA::MORFOLOGIA VEGETAL; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA::PRODUCAO E BENEFICIAMENTO DE SEMENTES; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA::PRODUCAO DE MUDAS; 15. Vida Terrestre